Team Work in the Education Organization: the Aspect of Pedagogues View - Gumuliauskienė, Aušrinė; Taputis, Evaldas (Acta Paedagogica Vilnensia, 2005)
One of the main point of contemporary modern education organization is team work. The main part of pedagogues thinks that the specific of education system is opportune for team work implantation. Education system organizations haven’t enough team work experience. The team work level in the education organization partly depends from style of the manager management. The main part of pedagogues well rated the team work, but there still not enough acquire suitable competence. In the education organizations by team work principle, dominate well-disposed working environment and friendly employees relation. Opportune rate team work action and commonly works in the teams these pedagogues that characterize peculiarities and capabilities necessary for such work. Pedagogues that have more team work experience and peculiarities necessary for the work in the team. The work team competence pedagogues are form by attending the classes and seminars. Often pedagogues choose team work in the project activity and in the show organization. The managers of the education organizations prefer employers which distinguish necessary peculiarities in the team. Friendly relation between colleagues form kindly environment for team action. Lots of pedagogues would like to develop team work competence. Pedagogues’ teamwork evaluation and action singularity in it depends on their age, work experience, group belong requirement, positive managers their action evaluation, organization style managing, manager initiative and other factors.